2017
DOI: 10.1186/s12885-017-3465-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiation in elderly esophageal cancer patients: rationale and design of a phase I/II multicenter study (OSAGE)

Abstract: BackgroundThe management of elderly patients with cancer is a therapeutic challenge and a public health problem. Definitive chemoradiotherapy (CRT) is an accepted standard treatment for patients with locally advanced esophageal cancer who cannot undergo surgery. However, there are few reports regarding tolerance to CRT in elderly patients. We previously reported results for CRT in patients aged ≥75 years. Following this first phase II trial, we propose to conduct a phase I/II study to evaluate the combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…This could be partially due to the fact that 36.2% of the patients recruited for their study had stage I or II tumors, whereas only 3.5% of the patients in our study had stage I or II. In the present review, the 5-year OS rate for chemotherapy and radiotherapy (23.6%) was significantly higher than that for radiotherapy alone (17.5%) ( p = 0.01), which is similar to other findings [ 24 , 25 ] and in accordance with the Radiation Therapy Oncology Group 8501 data [ 26 ]. At 5 years of follow-up, the OS for combined modality therapy was 26% compared with 0% after radiation therapy.…”
Section: Discussionsupporting
confidence: 92%
“…This could be partially due to the fact that 36.2% of the patients recruited for their study had stage I or II tumors, whereas only 3.5% of the patients in our study had stage I or II. In the present review, the 5-year OS rate for chemotherapy and radiotherapy (23.6%) was significantly higher than that for radiotherapy alone (17.5%) ( p = 0.01), which is similar to other findings [ 24 , 25 ] and in accordance with the Radiation Therapy Oncology Group 8501 data [ 26 ]. At 5 years of follow-up, the OS for combined modality therapy was 26% compared with 0% after radiation therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Although advanced age is not a contraindication for aggressive treatment, data on whether CRT is superior to RT alone for patients with unresectable or medically inoperable ESCC are scarce, and the efficacy of definitive CRT has not been established [16]. Zhao et al reported that CRT with platinum and 5-FU is well-tolerated and more effective than RT alone for elderly patients older than 75 years with locally advanced ESCC [17].…”
Section: Discussionmentioning
confidence: 99%
“…Trial NCT 02735057, conducted in France, was the only study that detailed their study protocol in another journal. 37 Among the nine studies, chronological age, comorbidity, and functional status were commonly established as notable markers for the assessment of the elderly. To our surprise, the inclusion criteria of malnutrition was only strictly restricted in three studies.…”
Section: Resultsmentioning
confidence: 99%